Invasive aspergillosis in a systemic lupus erythematosus patient - Setiyohadi, Bambang; Azizi, M S; Yuliani, Ika Wulan; Sukmana, N; Suhendro, Suhendro; Simadibrata, M; Rumende, C Matin; Sulaiman, A S; Wahyuningsih, R; Lisnawati, Lisnawati; Yudharto, M A; Anggraini, N; Oktaviana, F; Sandra, R (Indonesian Journal of Rheumatology, 2010)
Systemic lupus erythematosus (SLE) is an autoimmune disease with a broad clinicalmanifestation characterized by production of antibodies against cellular nuclear components. The prevalence of SLE among many countries is variable, ranging from 2.9 to 400 per 100,000. In Cipto Mangunkusumo General Hospital, the incidence of SLE between 1990 and 1998 is 37.3 per 10,000 hospitalization.1 Patients with autoimmune disease have at least twofold risk of acquiring infections compared with healthy individuals. This may be due to the immunosuppresant therapy but could also caused by the primary immune dysregulation that was the basis for the pathogenesis of their disease, or other autoimmune disease manifestations such as lymphopenia.2 Infection is the main factor increasing the mortality and morbidity of SLE patients. A study in New York conducted between 1966 and 1976 involving 223 SLE patients reported 150 cases of infection, of which 23 were opportunistic infection: 12 were candidiasis while 11 others were deep fungal infection. The use of corticosteroids in SLE is the main factor that predispose patients to infection, particularly fungal infection.3 Aspergillosis is the term used to denote all disease caused by any one of the pathogenic and allergenic species of Aspergillus. The annual incidence of aspergillosis in the United States is reported to be 1â2 per 100,000.4 Aspergillus fumigatus is the cause of most cases of invasive aspergillosis, almost all cases of chronic aspergillosis, and most allergic syndromes. The mortality rate of invasive aspergillosis is 50% when properly diagnosed and treated; otherwise it could be as high as 100%